2018
DOI: 10.5045/br.2018.53.3.233
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional retrospective study to analyze the underlying causes and clinical characteristics of children with reactive thrombocytosis at a Korean tertiary medical center

Abstract: BackgroundReactive thrombocytosis (RT) is a common condition among children, although no studies have examined the etiology or clinical characteristics of RT among Korean children.MethodsThis retrospective study evaluated children with RT at a single Korean tertiary center during a 10-year period.ResultsRT accounted for 13.5% of children who were admitted to the pediatric ward (4,113/30,355): mild RT, 82.7%; moderate RT, 14.1%; severe RT, 1.1%; and extreme RT, 2.1%. There was a negative correlation between pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
(40 reference statements)
1
6
0
Order By: Relevance
“…conversely, other authors have found that platelet counts do not correlate with disease severity and clinical outcome (68,69). Routine prophylactic anti-platelet treatment or further investigations are not necessary in children with RSV-positive bronchiolitis and thrombocytosis (61,68,70).…”
Section: Imaging Of Rsv Infectionmentioning
confidence: 95%
See 2 more Smart Citations
“…conversely, other authors have found that platelet counts do not correlate with disease severity and clinical outcome (68,69). Routine prophylactic anti-platelet treatment or further investigations are not necessary in children with RSV-positive bronchiolitis and thrombocytosis (61,68,70).…”
Section: Imaging Of Rsv Infectionmentioning
confidence: 95%
“…The most frequent causes of secondary thrombocytosis in childhood are acute respiratory tract infections (57)(58)(59)(60)(61). To date, several authors have reported significantly higher mean platelet counts in patients with RSV than in patients with other acute respiratory tract infections (61)(62)(63)(64). Thrombocytosis is more likely to occur in younger patients, who have clinical manifestations of wheezing and dyspnoea (62,64).…”
Section: Imaging Of Rsv Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…75 Thrombopoietin may be involved in this thrombopoiesis activation mechanism through its stimulation by IL-6. 76 Clinically, inflammation-related thrombocytosis is observed in infectious diseases 77 but also in non-infectious ones such as inflammatory bowel disease, 78,79 where a correlation has been found between plasma hepcidin levels and platelet counts, 80 auto-immune disorders (systemic lupus erythematosus, 81 juvenile arthritis 82 ), various malignancies including solid tumors, 83 or chronic myeloproliferative neoplasms, 84 in which thrombocytosis can also, of course, be of primary origin. As for the thrombotic risk, it may result from the conjunction of reactive thrombocytosis and the natural history of the causal disease.…”
Section: Acquired (Thalassemia/mds)mentioning
confidence: 99%
“…Moreover, many interleukins (IL) involved in the inflammation processes, mostly IL-6 and IL-11, can stimulate the platelet production in the liver [ 27 , 28 ]. These processes are highly active during childhood: ST is reported in 6–15% of hospitalized children, and up to 1% of children in intensive care units show platelet counts exceeding 1000 × 10 9 /L [ 5 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Reactive/secondary Thrombocytosis (St)mentioning
confidence: 99%